2001
DOI: 10.1002/arch.1065
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid‐induced facilitation of the proboscis extension reflex habituation in the honeybee

Abstract: Imidacloprid is a new insecticide from the family of the neonicotinoids, which interact with the insect nicotinic acetylcholine receptor. The effects of imidacloprid at a dose that does not affect sensory or motor functions are studied on non-associative learning abilities in the honeybee. The behavioral procedure is the habituation of the proboscis extension reflex (PER). Imidacloprid topically applied on the thorax (1 microl) at the doses of 5, 10, and 20 ng/bee induces an increase of the gustatory threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 14 publications
7
81
0
2
Order By: Relevance
“…Harnessed bees given only pure sucrose solution (control bees, Fig.1) had response thresholds similar to those measured in 1week old bees (Pankiw and Page, 2000;Scheiner et al, 2004). Lambin et al found that imidacloprid applied topically on the thorax at 1.25 or 2.5ngbee -1 does not significantly alter SR, although higher doses (5, 10 and 20ng) significantly reduce SR, particularly after 60min (Lambin et al, 2001). Bees are more sensitive to neonicotinoids given orally than applied topically (Decourtye and Devillers, 2010 Another study (Kirchner, 1999) noted that imidacloprid at concentrations of 20-100p.p.b.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Harnessed bees given only pure sucrose solution (control bees, Fig.1) had response thresholds similar to those measured in 1week old bees (Pankiw and Page, 2000;Scheiner et al, 2004). Lambin et al found that imidacloprid applied topically on the thorax at 1.25 or 2.5ngbee -1 does not significantly alter SR, although higher doses (5, 10 and 20ng) significantly reduce SR, particularly after 60min (Lambin et al, 2001). Bees are more sensitive to neonicotinoids given orally than applied topically (Decourtye and Devillers, 2010 Another study (Kirchner, 1999) noted that imidacloprid at concentrations of 20-100p.p.b.…”
Section: Discussionmentioning
confidence: 59%
“…Lambin et al topically applied imidacloprid on the thorax and found that it decreases SR at high doses of 5, 10 and 20ngbee -1 (Lambin et al, 2001). However, no honey bee studies have examined the effect of ingested imidacloprid on SR, or tested the effect of imidacloprid at lower doses that correspond to more realistic field exposure levels [1.1-4.3ngbee -1 (Rortais et al, 2005)].…”
Section: Introductionmentioning
confidence: 99%
“…Imidacloprid might also induce sublethal effects that might affect bees. In particular, it might modify the learning and orientation abilities of honeybees at concentrations as low as 0.1 ng/bee ) and 1.25 ng/bee (Lambin et al, 2001). However, these results might vary according to honeybees age , race (Suchail et al, 2000), colony , and season .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that IMD, is an agonist of the nicotinic acetylcholine receptor (nAChRs) on the postsynaptic membrane, and like other compounds from this group of pesticides, it affects the central nervous system (CNS) of insects (Brown, Ihara, Buckingham, Matsuda, & Sattelle, 2006;Matsuda, Shimomura, Ihara, Akamatsu, & Sattelle, 2005) and subsequently the insect's physiology and behavior (Desneux, Decourtye, & Delpuech, 2007;Piiroinen & Goulson, 2016;Teeters, Johnson, Ellis, & Mario, 2012;Van Dijk, Van Staalduinen, & Van der Sluijs, 2013). For example, it has been shown that sublethal doses of IMD have an adverse effect on the bee's sense of smell and memory (Decourtye, Devillers et al, 2004, Decourtye, Armengaud et al, 2004Kirchner, 1999;Williamson, Baker, & Wright, 2013), as well as on the insects' intensity of feeding (Schneider, Tautz, Gruenewald, & Fuchs, 2012;Yang, Chuang, Chen, & Chang, 2008), territorial disorientation (Hatjina, Papachristoforou, Charistos, Bouga, & Arnold, 2012;Henry et al, 2012), and neurophysiologic changes (Goulson, 2013;Guez, Suchail, Gauthier, Maleszka, & Belzunces, 2001a, 2001bLambin, Armengaud, Raymond, & Gauthier, 2001). In recent in vivo studies, it has also been shown that the sublethal doses of imidacloprid not only cause decrease in the size of HPGs but also in the respiratory rhythm of A. mellifera (Hatjina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%